The role of feed solution chemistry and draw solution types on the forward osmosis membranes fouling - Li, Qinghua. (2011)
Forward Osmosis (FO), a natural osmotically driven process, is attracting increasing interest for its potential applications in water and wastewater treatment and desalination due to its low energy consumption. Internal concentration polarization (ICP), a unique feature of FO, is one of the drawbacks that limit the widespread application of FO processes. The existence of ICP during FO process results in the non-linear relationship between FO flux and the apparent driving force, i.e. the concentration difference between the draw solution and the feed water. Membrane fouling is another challenge for the FO application. The coupled effect of membrane fouling and ICP significantly limits the FO flux efficiency, which were then systematically investigated in this study. Sodium alginic acid salt (Alginate), a macromolecule having great intermolecular adhesion calcium ions, was chosen as the model foulants. Corresponding experiments without foulant added were carried out to study the ICP, which is confirmed to be influenced by draw solution composites, e.g., concentration. Experiments with foulant added under similar experimental conditions were carried out to study FO membrane fouling influenced by both draw solutions and feed solution types. The experiment results are consistent with theoretical model prediction. It was found that the flux level, solution composition (divalent ions concentration as well as draw solution composites) and FO membrane orientation play a significant role on the organic fouling. A high initial flux level and presence on divalent ions in feed water promoted the alginate fouling on the porous support layer of the FO membrane. A critical flux phenomenon was observed for the concentration driven FO process, similar to the phenomenon observed in pressure-driven membrane process, where significant relative flux reduction occurred only when the water flux level exceeded some threshold value. The experimental results show that the value of critical flux depends on both feed water and draw solution. The presence of Ca2+ brings the critical flux level down. The presence of NO3- in draw solutions brings the critical flux further down, due to the enhanced back diffusion of Ca2+ from draw solution to feed water. In addition, alginate fouling on the FO membrane was less severe with the active layer facing the feed solution than that with the active layer facing the draw solution. Based on the results observed and existing FO application, several fouling control methods and critical flux application were also summarized in the report.